The Specificity of Leadership Communication - Pantha, Shiva Raj (The International Research Journal of Management Science, 2018)
This paper analyzes and discusses the link between leadership and communication. Drawing the leadership specific communication traits into discussion, the paper announces that leadership communication is different from followership communication. Among many, three particular discussion points have been taken into account viz. memorability of messages, the use of business stories and nonverbal signals. Organizational leaders resort to the higher memorability of their messages using the stories and the strengthening of the messages is made possible through the stronger gestures, postures, eye movements and very congruent voices. Thus, this paper contends that leadership employs the communications patterns that are different from other executive positions in an organizational setting.